Effect of longitudinal-angular oscillations of the harvester-thresher separator on smooth motion of the reaper - Leonid M. Groshev; Svetlana A Partko; Andrey N. Sirotenko (Advanced Engineering Research, 2017)
Introduction. The effect of the low-frequency oscillations of the reaper on crop losses of the domestic combine harvesters is considered. In the study, various speeds of the machine, various mass-geometric and elastic-dissipative characteristics of the units are taken into account. The geometrics of the overhead system of the combine reaping section which ensures smooth running and reduces crop losses for the reaper is determined. Taking into account the mass-geometric and elastic-dissipative characteristics, the amplitude and frequency spectra of the oscillations of the domestic machines of the agroindustrial complex are determined. The mathematical dependence of the reaper oscillations on the combine operation conditions is proposed. Materials and Methods. The mathematical modeling of units vibrations is used with account for the longitudinal-vertical oscillations of the separator body and the heaving of the reaper. The equation in the frequency domain is solved. Research Results . A two-mass oscillatory model is constructed, and the corresponding differential equations of motion are obtained. The graphs of dependences of RMS loads on shoes with different parameters of the suspension are presented. The geometrics of the suspension system of the harvester reaping part ensuring smooth running and lower crop losses for the reaper, is established. The relationship between the change in the number of detachments of the shoes, the linear speed of the machine and the parameters of the reaper suspension is educed. Discussion and Conclusions . The conducted investigation allows drawing the following conclusions. Frequency characteristics of the shoes response are caused by parameters of the reaper and separator suspensions. The reaper suspension system in the domestic grain harvesters does not ensure the continuous operation of the reaper in the copy mode of the soil microrelief which leads to generating additional oscillations of the body and crop loss. The parasitic vibrations strength can be reduced by increasing the extension of the reaping part of the separator body and reducing the rigidity of the reaper suspension.